PERLINDUNGAN HUKUM DAN TANTANGAN KEBIJAKAN DALAM MENGATASI MUTILASI GENITAL PEREMPUAN TANPA INDIKASI MEDIS: Legal Protection and Policy Challenges in Addressing Female Genital Mutilation without Medical Indication - Istiqomah (VARIA HUKUM, 2024)
The practice of female genital cutting and injury (P2GP) without medical justification constitutes a violation of human rights and poses a high risk to women's physical and psychological health. Therefore, legal protection is necessary to regulate female genital mutilation (FGM) without medical indications. This study aims to analyze the legal protection for women against the harmful practice of P2GP and to identify challenges in policy implementation. The research methodology adopts a normative approach by analyzing legislation, international human rights instruments, and case studies from several countries that have implemented strict policies against P2GP. Additionally, this study is integrated with an empirical approach through interviews and surveys with affected women and relevant stakeholders. The findings indicate that although various legal instruments are in place, the effectiveness of legal protection still faces obstacles, such as weak law enforcement, cultural factors, and a lack of public awareness. Some countries have imposed strict sanctions on P2GP perpetrators; however, the success of implementation largely depends on social and political support. The study concludes that stronger legal reforms are necessary by clarifying and tightening regulations that prohibit female genital mutilation (FGM) without medical indications, including imposing stricter sanctions on perpetrators and involved parties. Furthermore, increased public education through awareness campaigns highlighting the negative impacts of P2GP on health and human rights is essential to eliminating the practice. The limitations of this study include restricted empirical data from certain regions that are difficult to access due to cultural barriers or limited data availability. The practical implications of this research include policy recommendations to strengthen regulation and law enforcement, while its social implications highlight the need for a paradigm shift in society regarding this deeply rooted practice.